The âThird Spaceâ of Education: History of Hizbul Wathan Muhammadiyah 1918-1949 - Muarif, Muarif (Muhammadiyah University Press, 2018)
As a product of social practice, the presence of Hizbul Wathan Muhammadiyah successfully fills the void between the dysfunction of formal education institution and the society. It is the contemplation of the input-output oriented paradigm of the former colonial education. In fact, a number of graduates suffer from reality faltering when they are directly involved in the society. Hizbul Wathan Muhammadiyah exists as the antithesis of the contradictory structure between formal schools and society. It fills the âthird spaceâ of education by serving as the intermediary to facilitate distinctive values, norms and collective consciousnessâwhich differ from general Scout movement. The ideology of religious humanism, nationalism, and patriotism in Hizbul Wathan Muhammadiyah has moved beyond others.